Primary undifferentiated pleomorphic sarcoma of the jejunal mesentery with a complicated course: A case report - Jochen Jure; Marc E Vuylsteke (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
A primary Undifferentiated Pleomorphic Sarcoma (UPS) of the mesentery is a rare form of malignancy, most commonly usually affecting the soft tissues of the extremities. Due to their location in the abdominal cavity distant from the intestinal loops they remain asymptomatic for a long time. In this study, an incidental finding on imaging is presented in a 66-year-old woman. CT imaging revealed a large mass in her abdomen, with difficulty pinpointing its exact origin. Exploratory laparotomy was performed to remove the mass in its entirety. Examination of the mass showed findings consistent with an undifferentiated pleomorphic sarcoma. She recovered well after her surgery. However, on follow-up imaging, a solitary metastatic lesion in her lung was detected. The prognosis of UPS is historically dismal with invasive treatment options currently being the preferred methods for management.